Teachers’ Beliefs on the Use of Project-Based Learning for Teaching Writing - Adiyani, Novasa; Febriyani, Suci; Hidayati, Nur (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The research was focused on investigating teachers’ beliefs regarding the implementation of Project Based Learning in teaching writing. In order to reach the objective and address the research inquiries, a qualitative case study. The research design is utilized to collect qualitative data. The study involved two English teachers from different schools in Indonesia teaching at the junior high school level. The first teacher was a new teacher with 2 years of experience and not certified yet, while the second teacher was an experienced teacher with 15 years of experience and certified in PPG. The study highlighted Project-Based Learning (PjBL) as an effective method for teaching writing in Junior High schools. The teachers support Project Based Learning for its alignment with the curriculum and its benefits in promoting critical thinking and problem-solving skills. PjBL also improved student motivation, engagement, and self-regulation. However, challenges such as progress monitoring, time management, and access to technology exist. Despite these obstacles, PjBL offered long-term advantages for students. In conclusion, PjBL was a valuable approach for teaching writing but requires careful planning and support for successful implementation. Keywords: Writing, Project-Based Learning, Beliefs